The Role of Open and Distance Learning (ODL) in Promoting Access to Women’s Education in Northwestern Nigeria: A Case Study of the National Open University of Nigeria (NOUN) - Adamu, Shehu Usman; Waziri, Bala Kwata; Adesina, Adewale; Iro, Babangida (West African Journal of Open and Flexible Learning, 2024)
A survey was conducted using the National Open University database to ascertain the number of women from the northwestern states of Jigawa, Kaduna, Kano, Katsina, Kebbi, Sokoto and Zamfara studying in the University based on the admission records from 2018 to 2022. The study also checked the faculties where those women registered during the last 4 years to determine the role of Open and Distance Learning in giving women access to higher education. A total of twenty-five thousand three hundred and sixteen women enrolled in the National Open University of Nigeria in the period under review with Kaduna Study Centre having the highest figure of 8,791, followed by Kano with 4,995 with Katsina, Dutse, Sokoto, Gusau and Birnin Kebbi having 2,554., 1,607., 1,129., 1,000 and 971 respectively while other smaller centres in Northwest had 4,263. Concerning programmes of study in various faculties, the Faculty of Health Sciences had the highest enrollment figures of ten thousand four hundred and twenty-four (10,424) representing 41.1% followed by the Faculty of Science with three thousand eight hundred and thirty-eight (3,838) representing 15.1%. Faculties of Agric, Arts, Education Law and Management had enrolment figures of 134 (0.52%), 634 (2.53%), 3,921 (15.4%8), 98 (0.38%), 2,954 (11.66%) respectively while Faculty of Social Sciences had 3,311 (13.07%). Generally, Open and Distance Learning has given women tremendous opportunities to higher education in the region considering that over twenty-five thousand women registered for various programmes using the ODL during the period under review. Résumé : Une enquête a été menée à l’aide de la base de données de l’Université Nationale Ouverte pour déterminer le nombre de femmes de l’État du Nord-Ouest de Jigawa, Kaduna, Kano, Katsina, Kebbi, Sokoto et Zamfa qui étudient à l’Université en fonction des dossiers d’admission de 2018 à 2022. L’étude a également examiné les facultés où ces femmes se sont inscrites au cours des 4 dernières années afin de déterminer le rôle de l’enseignement ouvert et à distance dans l’accès des femmes à l’enseignement supérieur. Un total de Vingt-cinq mille trois cent seize femmes inscrites à l’Université Ouverte du Nigéria au cours de la période considérée, le centre d’études de Kaduna ayant le chiffre le plus élevé de 8.791, suivi par Kano avec 4.995 avec Katsina, Dutse, Sokoto, Gusau et Birnin Kebbi totalisant 2554, 1 607, 1 129, 1 000 et 971 respectivement, tandis que les autres petits centres du Nord-Ouest comptaient 4 263. En ce qui concerne les programmes d’études dans diverses facultés, la faculté des sciences de la santé a eu les chiffres les plus élevés d’inscription de dix mille quatre cent vingt-quatre (10424) représentant 41,1 %, suivie par la faculté des sciences avec trois mille huit cent trente-huit (3838) représentant 15,1 %. Les facultés d’agriculture, des arts, du droit de l’éducation et de la gestion ont enregistré respectivement 134 (0,52 %), 634 (2,53 %), 3921 (15,4 %), 98 (0,38 %) et 2954 (11,66 %) inscriptions, tandis que la faculté des sciences sociales en a obtenu 3311 (13,07 %). Le programme d’enseignement ouvert et à distance a offert aux femmes de formidables possibilités d’accéder à l’enseignement supérieur dans la région, compte tenu du fait que plus de 25 000 femmes se sont inscrites à divers programmes utilisant le EOD au cours de la période considérée. Mots-clés : FOAD, Femmes, Éducation des femmes